Building transitions to post‐capitalist urban commons. Issue 4 (11th August 2016) - Chatterton, Paul
Abstract : This paper opens up a novel geographical research agenda on building transitions beyond the capitalist present. It brings into conversation two previously disconnected areas of academic debate: socio‐technical transition studies and more radical work on post‐capitalism. The paper offers empirical evidence of real‐life socio‐spatial practices that build postcapitalist socio‐technical transitions through a case study of the daily experiences, motives and values of residents in a community‐led cohousing project in the UK. I begin by exploring definitions around post‐capitalism and transition thinking, and then introduce the notion of the urban commons to point towards the geographies of post‐capitalist transitions and illustrate the kinds of social and spatial relations that underpin them. The paper then provides empirical substance for a geographical agenda around post‐capitalist transitions through the case study, highlighting themes of experimentation, transformation and direct democracy. The paper concludes with some strategic future reflections and makes a claim for a geographical research agenda that elaborates the possible radical geographies and place imaginaries of post‐capitalist transitions in our teaching, research and policy work. Unless geographers forge direct and necessary links between transitioning and moving beyond capitalism, our ability to take decisive and meaningful action on the challenges that lie ahead will be limited.